Utilizing Video Graphics as a Digital Learning Media to Improve Students' Green Skills - Mayrahma Lisdiantika; Josephine Tanesha; Mustika Nuramalia Handayani; Yasyfa Aulia Rustandi Putri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
This study aims to explain how video graphics-based digital learning media can be an alternative in the learning process that can meet the needs of green skills and support the concept of SDGs. The research used a literature review by collecting data from several articles, proceedings, and books from 2013-2022. The results showed that green skills could be applied in education by using environmentally friendly learning media. One of the learning media that can be used is videography. The use of videography can support the application of green skills by using the paperless principle in every learning activity. So, applying green skills in everyday life can attain several SDGs goals, such as innovation and climate action.